The Effect of Using Stick Figures on the Eighth Grade Students’ Reading Comprehension Achievement at SMPN 7 Bondowoso - Ramadhani, Novita Fitria; Tasnim, Zakiyah; Ariyanto, Sugeng (EFL Education Journal, 2016)
This research was intended to know whether or not there was a significanteffect of using stick figures on the eighth grade students’ reading comprehensionachievement at SMPN 7 Bondowoso in the 2015/2016 academic year. The research designwas Experimental Research. The research area was chosen by using purposive methodwhile cluster random sampling was used to determine the research respondents. The datawere collected by using a test, interview, and documentation. The collected data from thepost test were analyzed by using Independent Sample t-test with SPSS computing system.The analysis results showed that the significant value was 0.009 which was less than 0.05.From the hypothesis verification, it was known that there was a significant effect of usingstick figures on the eighth grade students’ reading comprehension achievement at SMPN 7Bondowoso in the 2015/2016 academic year.